CEISE Model: Integrating Islamic Values and Community Engagement for Service Excellence in Baitul Mal Wa Tamwil - Muktirrahman Muktirrahman; Maksum Maksum; Irtifatus Sholehah; Nurul Huda; Ishfaq Ahmed (Universitas Islam Negeri Madura, 2025)
Baitul Mal wa Tamwil (BMT) as Islamic microfinance institutions face challenges in creating sustainable service differentiation amid increasingly intense financial sector competition. This research develops the Community-Embedded Islamic Service Excellence (CEISE) Model as a theoretical framework to understand how the integration of Islamic values and community engagement creates competitive advantages in BMT operations. Using a qualitative case study approach at BMT NU East Java Pasongsongan Branch, the study involved in-depth interviews with 10 staff members and 15 customers, observation, and document analysis. Data were analyzed using the Miles and Huberman thematic analysis framework. Findings demonstrate that CEISE Model implementation through four main dimensions: Spiritual Service Dimension (SSD), Community Integration Mechanism (CIM), Adaptive Accessibility Framework (AAF), and Sustainable Intimacy Balance (SIB) successfully creates distinctive value propositions. Service innovations such as